Fifty years of the Department of Geography and the study of geography in Maribor - Horvat, Uroš (Journal for Geography, 2011)
The year 2011 marks the 50th years from establishment of the Academy of Education in Maribor. One of its successors is also Faculty of Arts, where is conducted the study of geography. The paper discusses the development of the Department of Geography and the study of geography in Maribor, which in fifty years passed through the various developmental periods: in the terms of organization, courses, research and human resources. The basic mission of the department, (training of personnel for teaching geography in primary and secondary schools) was conducted through using a variety of courses. In 1985 the Academy changed to Faculty of Education. With the establishment of the Faculty of Arts in 2006 the Department of Geography became part of it. The transition to new study programs, which have been prepared in accordance with the Bologna declaration, brought a series of innovations, as well as challenges; both for teachers and students.